Reconsidering Cochlear Implants: The Lessons of Martha’s Vineyard - Levy, Neil (Bioethics, 2002)
I distinguish and assess three separate arguments utilized by the opponents of cochlear implants: that treating deafness as a medical condition is inappropriate since it is not a disability; that so treating it sends a message to the Deaf that they are of lesser worth; and that the use of such implants would signal the end of Deaf culture. I give some qualified support to the first and second claim, but find that the principal weight of the argument must be borne by the third argument: that use of the cochlear implants is impermissible because Deaf culture is intrinsically valuable. I show that this claim is, in practice, incompatible with the claim that deafness is not a disability: that the significant disadvantages suffered by the hearing impaired can only be corrected by measures that would end Deaf culture. Since the potential recipients of cochlear implants are, in the main, the prelingually deaf children of hearing parents, the burden of banning the implants would be borne by people who are not members of Deaf culture, and who owe that culture nothing over and above what we all owe cultures in general. I conclude that we cannot ask the parents of these children to sacrifice the interests of their children for the sake of Deaf culture.